64.15.3 problem 3

Internal problem ID [13580]
Book : Differential Equations by Shepley L. Ross. Third edition. John Willey. New Delhi. 2004.
Section : Chapter 6, Series solutions of linear differential equations. Section 6.2 (Frobenius). Exercises page 251
Problem number : 3
Date solved : Tuesday, January 28, 2025 at 05:53:18 AM
CAS classification : [[_2nd_order, _with_linear_symmetries]]

\begin{align*} \left (x^{4}-2 x^{3}+x^{2}\right ) y^{\prime \prime }+2 \left (x -1\right ) y^{\prime }+x^{2} y&=0 \end{align*}

Using series method with expansion around

\begin{align*} 0 \end{align*}

Solution by Maple

Order:=6; 
dsolve((x^4-2*x^3+x^2)*diff(y(x),x$2)+2*(x-1)*diff(y(x),x)+x^2*y(x)=0,y(x),type='series',x=0);
 
\[ \text {No solution found} \]

Solution by Mathematica

Time used: 0.075 (sec). Leaf size: 71

AsymptoticDSolveValue[(x^4-2*x^3+x^2)*D[y[x],{x,2}]+2*(x-1)*D[y[x],x]+x^2*y[x]==0,y[x],{x,0,"6"-1}]
 
\[ y(x)\to c_1 \left (\frac {3 x^5}{10}+\frac {x^4}{4}+\frac {x^3}{6}+1\right )+c_2 e^{-2/x} \left (-\frac {429 x^5}{5}+\frac {91 x^4}{4}-\frac {31 x^3}{6}+3 x^2+1\right ) x^4 \]